SIU-ICUD: Focal Therapy for PCa — The Technique - Lara Rodriguez-Sanchez; Thomas J. Polascik; Kara Watts; Peter Ka-Fung Chiu; Mark Emberton; Behfar Ehdaie; Hashim U. Ahmed; Andre Abreu; Ardeshir R. Rastinehad; Rafael Sanchez-Salas (Société Internationale d’Urologie Journal)
Background/Objectives: Focal therapy (FT) and technology are closely connected. Advanced imaging allows for precise identification of the index lesion, enabling the targeted use of various thermal and non-thermal energy sources through different approaches, with specific techniques tailored to lesion location and operator expertise. This personalized approach enhances both safety and effectiveness, facilitating customized treatment planning. Methods: The International Consultation on Urological Diseases formed a committee to review the current literature on FT for prostate cancer (PCa), focusing specifically on the technique. Following in-depth discussions, the committee chose a “by lesion” approach rather than the traditional “by energy” approach to structure the review. A comprehensive PubMed search was conducted to gather relevant articles on the various energy modalities and procedural approaches used in FT for PCa. Results: Lesions in the apex, anterior, and posterior regions of the prostate can be accessed through several FT approaches, each associated with specific energy modalities and techniques. The transrectal approach utilizes high-intensity focused ultrasound (HIFU) and focal laser ablation (FLA), while the transperineal approach is compatible with energy sources such as cryotherapy, irreversible electroporation (IRE), brachytherapy, and FLA. The transurethral approach supports methods such as transurethral ultrasound ablation (TULSA). Each approach offers distinct advantages based on lesion location, treatment area, and energy modality. The choice of technique evaluated the safety and efficacy of each energy source and approach based on specific treatment areas within the prostate, highlighting the need for robust research across lesion locations and modalities, rather than focusing solely on each modality for a specific region. Conclusions: FT is rapidly advancing with new energy sources, technological improvements, and increasing operator expertise. To further optimize FT, research should prioritize evaluating the safety and effectiveness of different energy sources for various lesion locations, focusing on the treatment area rather than the energy modality itself.